Reduced sodium portions favor osteogenic properties and cytocompatibility of 45S5-based bioactive glass particles - Tsitlakidis, Stefanos; Hohenbild, Frederike; Saur, Merve; Moghaddam-Alvandi, Arash; Kunisch, Elke; Renkawitz, Tobias; Gonzalo-Juan, Isabel; Westhauser, Fabian (Biomimetics, 2023)
Besides its favorable biological properties, the release of sodium (Na) from the well-known 45S5-bioactive glass (BG) composition (in mol%: 46.1, SiO2, 24.5 CaO, 24.5 Na2O, 6.0 P2O5) can hamper its cytocompatibility. In this study, particles of Na-reduced variants of 45S5-BG were produced in exchange for CaO and P2O5 via the sol-gel-route resulting in Na contents of 75%, 50%, 25% or 0% of the original composition. The release of ions from the BGs as well as their impact on the cell environment (pH values), viability and osteogenic differentiation (activity of alkaline phosphatase (ALP)), the expression of osteopontin and osteocalcin in human bone-marrow-derived mesenchymal stromal cells in correlation to the Na-content and ion release of the BGs was assessed. The release of Na-ions increased with increasing Na-content in the BGs. With decreasing Na content, the viability of cells incubated with the BGs increased. The Na-reduced BGs showed elevated ALP activity and a pro-osteogenic stimulation with accelerated osteopontin induction and a pronounced upregulation of osteocalcin. In conclusion, the reduction in Na-content enhances the cytocompatibility and improves the osteogenic properties of 45S5-BG, making the Na-reduced variants of 45S5-BG promising candidates for further experimental consideration.